PENGARUH PENAMBAHAN TEPUNG AMPAS TAHU TERHADAP UJI ORGANOLEPTIK NUGGET AYAM - Andrian Nuredy; Nita opi ari kustanti; Dhenok Wahyu Lestari (AVES: Jurnal Ilmu Peternakan, 2019)
This research was conducted in the laboratory of the Faculty of Animal Husbandry at Balitar Islamic University.The purpose of this study is to know the result of the addition of pulp flour tofu to organoleptic test (smell, texture, color and flavor).The benefits of this research is the author hopes can be an input for the reader about chicken nuggets with the addition of pulp flour tofu as a good food, there are animal proteins and vegetable proteins. Increase the value of pulp know as a product of nugget. The material used is a nugget with the addition of pulp flour tofu 0%, 7.5%, 12.5%, and 17.5%. The method used is experimentation, with this study there are variable control and variable experiments as a reference between the initial state and the status of the treatment.The results of this study indicate a very real effect on the smell and taste of chicken nuggets by adding tofu pulp. the preferred odor of nuggets is the P0 treatment (0% tofu waste flour), while the color of the nugget favored by the panelists is the P1 treatment (7.5% tofu waste flour). Significantly different in texture with P0 and P3 (0% and 17.5% tofu pulp) and not significantly different in the color of chicken nuggets with the addition of tofu pulp with the most preferred treatment was P1 (7.5% tofu pulp)